Educating Teachers for the New Millennium? - Teacher training, ICT and digital competence - Cathrine Edelhard Tømte (Universitetsforlaget, 2015)
In this study we explored how teacher education institutions handle the use of ICT in teacher education. A qualitative approach conducted as a multiple case study design involved three teacher education institutions. Two case studies where conducted in 2009 and one in 2012. Findings revealed that teachers appear to have become more aware of the use of ICT in education in 2011 compared to 2009. Still, teacher students remain to be sufficiently well prepared on how to use ICT for pedagogical purposes, even if their technical skills are improved over the years.